Studi Ecological Fiscal Transfer sebagai Potensi Pendanaan Lingkungan di Daerah - Joko Tri Haryanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2015)
Along with the issue of the increasing prosperity in many parts of the world, including Indonesia, the globaldevelopment agenda has been shift ed from proverty issues to sustainable development goals (SustainableDevelopment Goal’s or SDG’s) issues. Consecutively, to support this target achievement, the role of thebudget becomes very signiﬁ cant, including the Transfer to the Region mechanism. Based on the analysis,the mechanism of the General Allocation Fund (DAU) has the potential to become a source of funding forenvironmental and ecological forestry. Ecological ﬁ scal transfer mechanism can be manifested through theaddition of DAU allocation for the beneﬁ t of environmental conservation and forestry. It also can be embodiedthrough the addition of environmental indicators and forestry in existing formulations of DAU.